Influence of smoking on the biolemmental status of young people - Zhyltsova, Yuliya; Turgunova, Bagila; Alayeva, Komila (Journal of the Belarusian State University. Ecology, 2025)
Data were obtained on the content of macro- and microelements in the organism of smoking and non-smoking young people aged 18-22. The results are important for the timely correction of the bioelement status of young people, for preserving and strengthening their health, and promoting a healthy lifestyle. It was found that the median concentrations for all studied elements (Ca, Cu, Fe, Mn, Zn, Cr, Pb, Cd и Hg) in the hair of smoking and non-smoking young people did not have statistical differences (p > 0.05). However, smoking young men were significantly more likely to have a deficiency of calcium (2 times, p = 0.05), manganese (1.05 times) and less likely to have a normal Fe content (1.1 times) than their non-smoking peers. Smoking girls were significantly more likely to have zinc deficiency (1.6 times) than non-smoking girls of the same age, whose calcium concentrations were 3.1 times more likely to be within the reference range. Smoking girls were significantly (p = 0.05) more likely to have an imbalance of elements such as Cu (excess), Fe (deficiency), Zn (deficiency) compared to smoking boys.